PEMBELAJARAN LAY UP SHOOT MENGGUNAKAN MEDIA AUDIO VISUAL BASIC LAY UP SHOOT UNTUK MENINGKATKAN HASILBELAJAR LAY UP SHOOT PADA SISWA KELAS VIIIA SMP KANISIUS PATI TAHUN 2013/2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the learning lay up shoot using basic audiovisual media shoot lay ups can improve learning outcomes shoot lay ups in class VIIIA Starch Canisius junior year 2013/2014 . This study uses Classroom Action Research ( CAR). The technique of collecting data through observation and assessment of learning outcomes shoot basketball lay up. Data analysis techniques used in this research is descriptive . At the end of the first cycle activity of teachers in teaching basic techniques lay up shoot using audio-visual media reaches 76.19%, whereas at the end of the first cycle of student activity during the learning process lay up shoot using audio-visualmediareaches78.57%. At the end of the second cycle of activity of teachers in teaching basic techniques lay up shoot using audio-visual media reaches 85.71%, whereas at the end of the second cycle of activity of students during the learning process lay up shoot using audio-visual media reaches 92.86%. Based on the results of the study it can be concluded that learning the lay-up shoot using basic audiovisual media shoot lay ups can improve student learning outcomes at Canisius junior class VIIIA Pati year 2013/2014